Unconventional design of the mechanical crank press developed by the topology optimization - Raz, Karel; Cechura, Milan; Kubec, Vaclac (Manufacturing Technology Journal, 2020)
This article deals with the design optimization of the mechanical crank press. These presses have not any signifi-cant development changes in a long time. Mechanical press LDC 250 with nominal force 2.5 MN (250 tons) was considered as an example. This type of press can be used for operations such as bending, drawing or cutting. The topology optimization was used during this research. This papers show advantage of this design method. The op-timized press has lower maximal Von-Mises stress in the structure and the maximal displacement is up to two times lower. The research was focused on the main frame (open frame with shape ?C?) of the press. The resistivity aga-ings vibrations was improved. The weight of the frame was not changed. The CAE tool NX Nastran and the opti-mization tool Frustum were used here. The workflow of the topological optimization is deeply described here. The comparison between the conventional (initial) and optimized design shows new approach to these machines.
Keywords: Forging; topology optimization; frame; design